2006
DOI: 10.1007/s10658-006-9069-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the aerial concentration and deposition of ascospores of Venturia inaequalis within a tree canopy during the rain

Abstract: Scab is an important disease of apple and its control depends almost exclusively on frequent use of fungicides. Primary scab infection in the spring assumes several steps: ascospore maturation, liberation of ascospores that become airborne, deposition on susceptible tissues, and infection. However, the spatial heterogeneity of ascospores within the tree canopy is unknown. Aerial concentration of ascospore (ACA), ascospore concentration in rain water (ACR) and ascospore deposition (AD) were therefore measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…1) and relationship between the logarithm of the observed variance s 2 f and logarithm of mean lesion density y f (b) (Eq. 2) for apple scab assessments on leaves sampled at different periods in Quebec, Canada from 1998 to 2007 dose (PAD), was aggregated within an orchard, by Carisse et al (2006) who reported that ascospore deposition within an apple tree was not randomly distributed following peaks of ascospore ejection, as well as by Carisse et al (2009) who found that betabinomial parameters p and θ could be calculated in 65% of data sets on number of scabbed leaves per shoot, while the binomial distribution provided the best fit for only 22% of the data sets. In the present study, a covariance analysis indicated that sampling season had a significant effect on the intercept parameter at the leaf scale meaning that the relationship between incidence and aggregation changed significantly over the course of the season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and relationship between the logarithm of the observed variance s 2 f and logarithm of mean lesion density y f (b) (Eq. 2) for apple scab assessments on leaves sampled at different periods in Quebec, Canada from 1998 to 2007 dose (PAD), was aggregated within an orchard, by Carisse et al (2006) who reported that ascospore deposition within an apple tree was not randomly distributed following peaks of ascospore ejection, as well as by Carisse et al (2009) who found that betabinomial parameters p and θ could be calculated in 65% of data sets on number of scabbed leaves per shoot, while the binomial distribution provided the best fit for only 22% of the data sets. In the present study, a covariance analysis indicated that sampling season had a significant effect on the intercept parameter at the leaf scale meaning that the relationship between incidence and aggregation changed significantly over the course of the season.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Charest et al (2002) showed that the primary inoculum is not uniformly distributed within an orchard. Furthermore, the same authors showed that airborne ascospore concentrations are aggregated within an orchard, and Carisse et al (2006) showed that ascospore deposition within an apple tree was aggregated during the peak of ascospore release. From these results, one may assume that apple scab incidence and lesion density are spatially aggregated in orchards; however, the robustness of this assumption must be evaluated.…”
Section: Introductionmentioning
confidence: 96%
“…Ascospore maturity could be assessed by visual observations of pseudothecia and release by spore trapping. Work by Carisse et al (2006) and Charest et al (2002) on spatial distribution of airborne ascospores suggested that several traps would be required because of spatial heterogeneity in inoculum density and that the detection threshold may be lower than the density of airborne ascospores in a well-managed orchard. In addition, information of airborne ascospore concentration has no predictive value because by the time the information become available, infection already took place.…”
Section: Models For Estimating Ascospore Maturitymentioning
confidence: 99%
“…Finally, the last ascospores mature until exhaustion of the stock in pseudothecia. In practice, there is so much variation in the proportion of mature ascospores between leaves and among cultivars (Fig.5.) (Carisse et al, 2006) that degree days were used to determine the period of availability of ascospores from about 50 to 350 CDD. At 350 the DDSS assume that over 95% the ascospore supply is depleted if sufficient rain events have occurred).…”
Section: A Ddss That Integrates the Three Components Of The Apple Scamentioning
confidence: 99%
“…Airborne inoculum was assessed in association with apple scab incidence in a study by Carisse et al (2007), but was not found to be correlated with incidence when monitoring was conducted only at the end of the primary infection period (green tip to calyx stage). The two main construction types of traps available are the vacuum or volumetric spore trap (VST) and the rotating-arm impaction spore sampler (Rotorod; Hirst and Stedman 1961;Zuck and Caruso, 1984;Aylor 1993).…”
Section: Introductionmentioning
confidence: 99%